2005
DOI: 10.1001/archinte.165.11.1222
|View full text |Cite
|
Sign up to set email alerts
|

Is Proton Pump Inhibitor Testing an Effective Approach to Diagnose Gastroesophageal Reflux Disease in Patients With Noncardiac Chest Pain?

Abstract: The use of PPI treatment as a diagnostic test for detecting GERD in patients with NCCP has an acceptable sensitivity and specificity and could be used as an initial approach by primary care physicians to detect GERD in selected patients with NCCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
14

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 47 publications
0
46
1
14
Order By: Relevance
“…Almost all gastroenterologists in this survey encountered patients presented with NCCP in (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) the preceding 6 months. The majority stated that the number of NCCP patients was increasing and the most common cause of NCCP was GERD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all gastroenterologists in this survey encountered patients presented with NCCP in (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) the preceding 6 months. The majority stated that the number of NCCP patients was increasing and the most common cause of NCCP was GERD.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Empirical PPI trial has been shown to be a simple, sensitive, non-invasive and cost-effective diagnostic test for GERD-related NCCP. [17][18][19][20] It is also uncertain whether chest X-ray is useful in evaluating the cause of NCCP in the absence of coexisting pulmonary symptoms such as cough, haemoptysis, shortness of breath and other symptoms. 8 Although not being used commonly as first-line test, specialized oesophageal testing such as 24 h pH study, manometry, barium swallow and Bernstein test were being used in quite a number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…8. Para o sintoma de dor torácica relacionado à suspeita de refluxo, recomenda-se uma tentativa com IBP duas vezes ao dia por 4 semanas (28) . 9.…”
Section: Anamneseunclassified
“…dor torácica for superior de 50% a 75% ou, eventualmente, valores superiores (43) . Concluindo, em estudo de WANG et al (41) foi demonstrado que o uso do teste terapêutico com IBP para o diagnóstico da DRGE, em particular para os pacientes com DTNC, tem aceitável sensibilidade e especificidade e pode ser usado como abordagem inicial para a detecção da DTNC relacionada à DRGE.…”
Section: Dtnc E Qualidade De Vidaunclassified
“…O papel da impedância esofágica intraluminar em pacientes com DTNC permanece por ser elucidado (41) .…”
Section: Phmetria Prolongada Phmetria Por Telemetria E Impedância Esunclassified